Methodologies for conducting research on giftedness - Thompson, Bruce, 1951-; Subotnik, Rena Faye (American Psychological Association, 2010)
"The editors envision this volume as a handbook for researchers in psychology and education who target exceptional populations in their work, and particularly individuals exhibiting gifts and talents. The research tools described here can help to move the scholarship on giftedness and talent development to a new level of rigor and encourage the testing of program models, as well as predictive validity of theoretical or conceptual frameworks (see for example Sternberg & Davidson, 2005). Of course, the methods described in these chapters can also be usefully applied in general populations or in studies dealing with specialized subpopulations other than gifted and talented. The scholars who contributed to the first nine chapters of this volume are pioneers in the field of measurement and statistics, and they show us most elegantly how the methodologies they have mastered or developed can apply to samples that, by their nature, make statistical analysis more challenging. We tasked our contributors to address the following four barriers, and one facilitator, associated with gifted education research: Definitions of giftedness and talent are not standardized; Test ceilings can be too low to measure progress or growth; Comparison groups are difficult to find for extraordinary individuals; Participant attrition in longitudinal studies may compromise tests of hypothesized effects; and, Qualitative research conducted with gifted populations can be enhanced due to highly articulate study participants"--Introduction. (PsycINFO Database Record (c) 2010 APA, all rights reserved).